Gender perspective in philosophy - Sonia Reverter Bañón (Feminismo/s, 2003)
Ever since the 70s women’s studies have made it increasingly and patently clear that the variable gender/sex cannot be left aside in any serious research. What has been coined «the feminist perspective» has as its origin the awareness that this variable must necessarily be included in any theoretical construct that may attempt to explain and/or question reality. This article analyses the consequences of the influence of the feminist perspective in philosophical circles. Our main interests herein are to examine how the irruption of feminism has questioned philosophical thought and to examine the framework of reconstruction that it can offer us when thinking through what has not been thought through by orthodox philosophy.